2021
DOI: 10.1093/ije/dyab008
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing a two-pronged epidemic in Mexico of non-communicable diseases and SARS-Cov-2: factors associated with increased case-fatality rates

Abstract: Background People with a previous diagnosis of non-communicable diseases (NCDs) are more likely to develop serious forms of COVID-19 or die. Mexico is the country with the fourth highest fatality rate from SARS-Cov-2, with high mortality in younger adults. Objectives To describe and characterize the association of NCDs with the case-fatality rate (CFR) adjusted by age and sex in Mexican adults with a positive diagnosis for SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…Country-specific patterns in these shifts caused by socioeconomic factors provide detail in the changing landscape of this disease ( Leong et al, 2021 ). In Mexico, there appear to be more diseased young men than anywhere else, this is likely due to an underlying epidemic of non-communicable diseases, such as obesity and diabetes ( Monterrubio-Flores et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Country-specific patterns in these shifts caused by socioeconomic factors provide detail in the changing landscape of this disease ( Leong et al, 2021 ). In Mexico, there appear to be more diseased young men than anywhere else, this is likely due to an underlying epidemic of non-communicable diseases, such as obesity and diabetes ( Monterrubio-Flores et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is considering that a similar number of people were tested among all quintiles. Thus, it reveals under-testing in those most vulnerable and an unequal distribution of a valuable resource, which adds another layer to the mortality disparity seen between private and public health-care systems in Mexico [25][26][27] . A study performed in Cameroon showed high sensitivity of POC tests when performed within 7 days of symptom onset 28 .…”
Section: Discussionmentioning
confidence: 99%
“…One study in Mexico used a multimorbidity perspective to estimate the risk of mortality from COVID [29]. Authors found that adults aged 20-39 years with three chronic diseases presented 16.1 (95% CI: 13.8, 18.7) times higher risk of death, adults aged 40-59 years presented 4.2 (95% CI: 4.0, 4.4) and adults 60-80 years 1.6 (95% CI:1.6 1.7), compared to disease-free individuals of the same age group.…”
Section: Discussionmentioning
confidence: 99%